3D Printing of Powder‐Based Inks into Functional Hierarchical Porous TiO2 Materials. Issue 3 (11th November 2019) - Xu, Chenyang; Liu, Ting; Guo, Wei; Sun, Yinghui; Liang, Chu; Cao, Kunli; Guan, Tianfu; Liang, Zhiqiang; Jiang, Lin
Abstract : Integrating multifunctional semiconducting metal oxide powders into a 3D printing technique to construct hierarchical porous structures is highly desirable and remains a significant challenge. Herein, an extrusion‐based 3D printing strategy is developed that can assemble TiO2 powders into hierarchical porous structures with multiscale pores at both the macro‐ and microscale. Powder‐based TiO2 inks with a significant shear‐thinning behavior and adequate storage modulus and yield stress are developed to meet the requirements of 3D printing of TiO2 in an air environment without the need for an additional solidification treatment, which provides good printing flexibility. The hierarchical porous structures with a relatively high compressive strength provide the 3D‐printed TiO2 structures with great potential for use in many applications, including filtration, thermal insulation, biomedical scaffolds, catalyst supports, and energy conversion. Compared with scaffolds with a compact morphology, the hierarchical porous TiO2 scaffold as a photoelectrode achieves a higher nitrogen photofixation yield due to its high surface adsorption and activation capacity caused by its porous morphology. Importantly, the powder‐based ink design and extrusion‐based 3D printing approach are readily extended to other semiconducting metal oxides such as ZnO and their composites. Abstract : An extrusion‐based 3D printing strategy is demonstrated to assemble TiO2 powders into hierarchical porous structures with multiscale pores at both the macro‐ and microscale. Compared with scaffolds with a compact morphology, the hierarchical porous TiO2 scaffold as a photoelectrode achieves a higher nitrogen photofixation yield due to its high surface adsorption and activation capacity caused by its porous morphology.